Kesesuaian Metode Fonik pada Konten Video Kinderflix Episode Fonik dalam Pembelajaran Membaca Permulaan Peserta Didik - Aprilia Ayu Nurcahyani; Joko Daryanto; Endrise Septina Rawanoko (Didaktika Dwija Indria, 2026)
Early reading instruction for elementary school students requires appropriate methods to ensure that the ability to recognize letters, sounds, and word blending develops optimally. One effective approach is the phonic method, which emphasizes the relationship between letters and sounds. Along with technological developments, audiovisual media such as educational videos have become a supporting alternative for learning. This study aims to analyze the suitability of the phonic method used in the video content of Kinderflix Phonic Episode for early reading instruction among elementary school students. This study used a descriptive qualitative approach with content analysis methods. Data were collected through observation of the Kinderflix Phonic Episode video content, documentation, and interviews with first-grade teachers at SDN Gumpang 03 Kartasura. Data analysis was carried out through data reduction, data display, and drawing conclusions. The results showed that the Kinderflix Phonic Episode video contains the main elements of the phonic method, such as introducing letter-sound relationships, blending sounds into syllables, and practicing reading simple words. In addition, the video content was deemed suitable for the characteristics of students' early reading stages, particularly in visual, auditory, and material repetition aspects. These findings indicate that the Kinderflix Phonic Episode video is relevant for use as a supporting medium for early reading learning because it helps students understand phonic concepts in a more engaging and interactive way that aligns with their stage of reading development.